2018
DOI: 10.1002/acp.3498
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric analysis of the recovered memory controversy in the 21st century

Abstract: Step 1: An extensive search was made with a list of keywords related to the repressed/recovered memory controversy. Only articles that contained one of these keywords were retrieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 107 publications
0
19
0
Order By: Relevance
“…There are two indications that this is not the case. First, in a recent bibliometric analysis, Dodier (2019) examined the number of publications and citations regarding repressed and recovered memories from 2001 to 2018. The author found that proponents and opponents of repressed memories have continued to publish articles about repressed and recovered memories throughout the time period.…”
Section: Memory Wars In the Courtroom And Beyondmentioning
confidence: 99%
“…There are two indications that this is not the case. First, in a recent bibliometric analysis, Dodier (2019) examined the number of publications and citations regarding repressed and recovered memories from 2001 to 2018. The author found that proponents and opponents of repressed memories have continued to publish articles about repressed and recovered memories throughout the time period.…”
Section: Memory Wars In the Courtroom And Beyondmentioning
confidence: 99%
“…A recent bibliometric analysis of articles on the recovered-memory controversy published in the 21st century ( Dodier, 2019 ) distinguished between articles that were skeptical of repression and those that were “sympathetic” to it. How this sympathy was defined or measured was not stated.…”
Section: Who Refers To Repression As a Theoretical Construct?mentioning
confidence: 99%
“…American Psychiatric Association, 2013, see also Otgaar et al, in press). Indeed, some 21st century authors still appear to adopt the view that trauma memories can be stored and become inaccessible for a long period of time-sometimes decades-before it becomes recoverable (Brand et al, 2018;Dalenberg et al, 2012;DePrince et al, 2012; see also Dodier, 2019, for a review of the evolution of the 21st century publications related to the recovered memory debate).…”
Section: The Scientific Status Of Repressed Memoriesmentioning
confidence: 99%
“…Although repression is not a sufficiently proven phenomena and scepticism is abound in the scientific literature (Dodier, 2019), several types of psychotherapies are partly aimed at helping patients to recover repressed memories. As Patihis and Pendergrast (2019) pointed out, it is very rare for therapists to explicitly state that the objective of their therapeutic techniques is to dig up memories buried in the unconscious.…”
Section: Recovered Memory Therapy and Beliefs About Repressed Memorymentioning
confidence: 99%